Enhanced spin hall effect in S-implanted Pt - Shashank, Utkarsh (2023)
High efficiency of charge–spin interconversion in spin Hall materials is a prime necessity to apprehend intriguing functionalities of spin–orbit torque for magnetization switching, auto-oscillations, and domain wall motion in energy-efficient and high-speed spintronic devices. To this end, innovations in fabricating advanced materials that possess not only large charge–spin conversion efficiency but also viable electrical and spin Hall conductivity are of importance. Here, a new spin Hall material designed by implanting low energy 12 keV sulfur ions in heavy metal Pt, named as Pt(S), is reported that demonstrates eight times higher conversion efficiency as compared to pristine Pt. The figure of merit, spin Hall angle (θSH), up to of 0.502 together with considerable electrical conductivity of 1.65 × 106 Ω–1 m–1 is achieved. The spin Hall conductivity increases with increasing , as , implying an intrinsic mechanism in a dirty metal conduction regime. A comparatively large of 8.32 × 105 (